2019
DOI: 10.1029/2018jg004875
|View full text |Cite
|
Sign up to set email alerts
|

Major Processes Shaping Mangroves as Inorganic Nitrogen Sources or Sinks: Insights From a Multidisciplinary Study

Abstract: Mangrove wetlands support numerous ecosystem services including nutrient cycling and carbon sequestration and storage (blue carbon). Mangrove sediments may serve as a nitrogen source or sink to the hydrosphere and atmosphere at both regional and global scales. However, major mechanisms controlling the connection between the mangrove and the adjacent tidal creek (nitrogen cycling in sediments and outfluxing) remain unclear. A multidisciplinary study based on intensive investigation, incorporating detailed sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 62 publications
0
18
1
Order By: Relevance
“…Given the above, plant biomass should, at least in theory, be positively correlated with CH 4 flux. This hypothesis is supported by several individual studies from salt marsh (e.g., Cheng et al, 2007; Hirota et al, 2007; Li, Wang, et al, 2018; Wang et al, 2019) and mangrove ecosystems (Alongi et al, 2008). There is currently no evidence of a similar relationship in seagrass ecosystems.…”
Section: Driversmentioning
confidence: 70%
“…Given the above, plant biomass should, at least in theory, be positively correlated with CH 4 flux. This hypothesis is supported by several individual studies from salt marsh (e.g., Cheng et al, 2007; Hirota et al, 2007; Li, Wang, et al, 2018; Wang et al, 2019) and mangrove ecosystems (Alongi et al, 2008). There is currently no evidence of a similar relationship in seagrass ecosystems.…”
Section: Driversmentioning
confidence: 70%
“…Prior studies assessing nutrient dynamics in other mangrove tidal creeks reported similar patterns (i.e. discharge of N-NH 4 + ), with the only difference being that P-PO 4 3− porewater discharge was sometimes measured (Dittmar, 1999;Gleeson et al, 2013;Maher et al, 2016;Ovalle et al, 1990;Tait et al, 2017;Wang et al, 2019). The tidal creek N-NH 4 + concentrations at low tide (7.9 μM [0; 50.7]) were significantly lower than the porewater concentrations at the mudflat stand (21.1 μM [0.5; 162.4]) and not significantly higher than those of the two vegetation stands (3.0 μM [1.7; 5.3] for Rhizophora; 4.3 μM [1.0; 6.0] for Avicennia) (Table 1).…”
mentioning
confidence: 84%
“…Although our study focuses on dissolved inorganic nutrients as they account for the preferential form consumed by primary producers, some studies have shown that dissolved organic nutrients could be assimilated, particularly in nutrient-limited conditions (Glibert et al, 2004;Vonk et al, 2008). Dissolved organic nitrogen and dissolved organic phosphorus concentrations are within the same order of magnitude of the dissolved inorganic fraction in undisturbed mangrove tidal creeks (Dittmar and Lara, 2001b;Gleeson et al, 2013;Tait et al, 2017), and of lower importance in sites with upstream activities generating nutrients input (Wang et al, 2019). Therefore, it is possible that organic nutrients also contribute, to some extent, to the aquatic productivity in mangroves before mineralization.…”
Section: Seasonal Variability Of Phosphate In the Tidal Creekmentioning
confidence: 99%
See 2 more Smart Citations